2006
DOI: 10.5089/9781451864007.001
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Misalignment: An Application of the Behavioral Equilibrium Exchange Rate (Beer) to Botswana

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. Botswana's successive currency devaluations and recent move from a fixed to a crawling peg exchange rate regime raise the question of whether the exchange rate might be misaligned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…It is important to note that our initial Johansen cointegration tests with all the fundamentals in the system recorded more than one cointegrating relationship in Nigeria, Sierra Leone, and Guinea. 15 It is well established in the literature that the existence of multiple cointegrating vectors complicates the interpretation of the equilibrium relationship between the REER and its fundamental determinants and presents the problem of identification (Johansen 1992;Iimi 2006). Therefore, we addressed the above problem by omitting the (0) variable, rir, from the cointegrating vector, while yielding just one cointegrating relationship.…”
Section: In Wamz Countriesmentioning
confidence: 99%
“…It is important to note that our initial Johansen cointegration tests with all the fundamentals in the system recorded more than one cointegrating relationship in Nigeria, Sierra Leone, and Guinea. 15 It is well established in the literature that the existence of multiple cointegrating vectors complicates the interpretation of the equilibrium relationship between the REER and its fundamental determinants and presents the problem of identification (Johansen 1992;Iimi 2006). Therefore, we addressed the above problem by omitting the (0) variable, rir, from the cointegrating vector, while yielding just one cointegrating relationship.…”
Section: In Wamz Countriesmentioning
confidence: 99%
“…Similar methodology was applied by Clark and MacDonald (1998), Baffes, Elbadawi and O Connell (1999), Maesofernandez, Osbat and Schnatz (2001), Dufrenot and Yahuoe (2005). Recently, Iimi (2006) and Iossifov and Loukoianova (2007) applied similar approach in Botswana and Ghana, respectively. For the purpose of this paper, real exchange rate is assumed to follow the path dictated by economic fundamentals, that is, while real exchange rate (rer) remains the only endogenous cum exogenous variable, the exogenous variables include net foreign assets (nfa), terms of trade shocks (tot), index of crude oil price volatility (iov), government s fiscal spending (gov), real foreign reserve (rsv) and index of monetary policy performance.…”
Section: Research Methodsologymentioning
confidence: 99%
“…The driving fundamental variables in their models were long term real interest rates differentials, productivity, net foreign assets, relative fiscal stance, real price of oil, and relative total consumption differentials. Iimi (2006) used the BEER methodology and found that the Botswana s pula seems to have been undervalued in the late 1980s and overvalued by 5 to 10 percent in recent years, though the misalignment in the 1990s seems to have been very marginal. Although the researcher used fewer fundamental variables for fear of loss of degree of freedom, it should still be recognized that these pieces of evidence were arrived at from a sample comprising of only 19 observations (1985 2004).…”
Section: Literature Review and Theoretical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Baffes et al (1999) computed misalignment for Côte d'Ivoire and Burkina Faso using single equation time series, Côte d'Ivoire's actual real exchange rate was found to be overvalued by 34% on average between 1987 and 1993. Iimi (2006) using the BEER approach found the Botswana's currency to be undervalued before 1980s and overvalued by 5% to 10% in the recent years. Fatma Marrakchi Charfi (2008) examined the misalignment for the case of Tunisia using the BEER, she found that Tunisian dinar's behaviour in the long-run was influenced by the net capital inflows, terms-of-trade shocks, and the productivity differential.…”
Section: Previous Studies Findingsmentioning
confidence: 99%